Taking Matters into Their Own Hands: The MST and the Workers’ Party in Brazil (Alternautas, 2015)
Brazil’s Movement of Landless Rural Workers (Movimento de Trabalhadores Rurais Sem Terra do Brasil—MST) has long engaged in a subtle form of brinkmanship with the Brazilian state and with the rule of law. The strange combination of audacity and vulnerability that characterizes this strategy is even more delicate in the context of the fourth straight mandate of the MST’s erstwhile political ally, the Workers’ Party (Partido dos Trabalhadores—PT). The great hope born in the MST that a PT administration would wholeheartedly support agrarian reform and thus make the MST strategy of land occupation and civil disobedience mostly unnecessary was to be utterly disappointed. As a result the MST must both challenge and yet tacitly support the PT for fear of the alternatives, all of which are worse. In this article the author concludes that the MST effectively implements a strategy that all at once creates authentically socialist agricultural settlements while simultaneously using the state to forward its goals.